Pengaruh Facility layout terhadap Customer satisfaction Melalui Variabel Mediator Service Quality - Chrissia, Andien Dammarist Eka; Riandi , Muhammad Hafiz (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The objective of this research is to perceive the direct and indirect impacts of facility layout on customer satisfaction with the mediation of service quality. The population of this quantitative causal research is the customers of Balai Kopi, a coffee shop in Malang City. The research samples were selected using purposive sampling technique with the criteria of people who have visited the coffee shop during the period of August – November 2023 and have made offline purchase at the shop. The results of the analysis indicate (1) that facility layout positively influences customer satisfaction, (2) that facility layout positively affects service quality, (3) that service quality positively impacts customer satisfaction, and (4) that facility layout positively influences customer satisfaction with the mediation of service quality. The theoretical implication of this study is deeper understanding on the effects of facility layout on customer satisfaction with the mediation of service quality. Facility layout must support service quality to optimally increase customer satisfaction. Further, the findings imply that upgrades in facility layout can directly enhance customer satisfaction, but the mediation effect of service quality is stronger. Therefore, companies, including Balai Kopi, are recommended to focus more on the establishment of service quality through excellent facility layout. Abstrak Penelitian ini bertujuan untuk memahami dampak langsung dan tidak langsung dari facility layout terhadap customer satisfaction, dengan variabel mediator berupa service quality. Pendekatan penelitian yang digunakan adalah kuantitatif. Populasi dalam penelitian ini adalah konsumen Balai Kopi Kota Malang. Teknik sampling yang digunakan adalah purposive sampling dengan kriteria konsumen Balai Kopi yang berkunjung secara offline pada bulan Agustus sampai November 2023 dan pernah melakukan pembelian offline. Hasil penelitian menunjukkan bahwa facility layout berpengaruh positif terhadap customer satisfaction, facility layout berpengaruh positif terhadap service quality, service quality berpengaruh positif terhadap customer satisfaction, dan facility layout berpengaruh positif terhadap customer satisfaction dengan service quality berperan sebagai mediator. Implikasi teoritis dari penelitian ini adalah pemahaman yang lebih mendalam mengenai pengaruh layout terhadap customer satisfaction dengan service quality sebagai mediator. Facility layout harus mendukung service quality untuk meningkatkan customer satisfaction secara optimal. Secara praktis, hasil penelitian menunjukkan bahwa pembenahan facility layout dapat secara langsung meningkatkan customer satisfaction, tetapi efek mediasi service quality lebih kuat. Oleh karena itu, perusahaan, termasuk Balai Kopi Kota Malang, disarankan untuk fokus pada pembentukan service quality melalui facility layout yang baik.